MEMAHAMI ALAT KELENGKAPAN DPRD SEBAGAI PRASYARAT PRODUK HUKUM (Analisis Terhadap Alat Kelengkapan DPRD Kabupaten Pandeglang) - Encep Mahfud Encep Mahfud (NIAGARA Scientific Journal, 2016)
The Regional People's Representative Council (DPRD) is a high-ranking regional institution whose position is very strategic in the regional government structure in formulating legal policies at the regional level. To support its performance, the Regional People's Representative Council (DPRD) forms work units, and these work units are called DPRD equipment. The equipment remains composed. Leadership of DPRD members, DPRD Commissions, Deliberative Body (Bamus), Household Affairs Agency (BURT), Legislative Body, Inter-Parliamentary Cooperation Agency (BKSAP), and Budget Committee. The DPRD apparatus has the task of assisting the DPRD institution in every policy making, as a legal prerequisite for a regional regulation. Apart from that, he also has the authority to serve in the DPR's internal environment and duties in the DPR's external environment. The duties of the internal leadership environment are: Develop work plans and divide work between the Chair and Deputy Chair, and announce them at the Plenary Meeting. This writing method is a qualitative method based on a causal-effectual model. The discussion used is to explain phenomena or describe variables and then analyze the relationship between the duties and functions of DPRD equipment in the formulation of regulations and legislation in the region. Pandeglang Regency. Research shows that the DPRD equipment is a very important institutional unit, a prerequisite for ratifying a regional regulation in the Pandeglang Regency DPRD.